Working Capital Turnover on Profitability Evidence on Manufacturing Firms in ASEAN - Aseng, Andrew Christian; Pandeirot, Lanemey Brigitha (SAFE-Network, 2023)
This research aims to find out the effect of working capital turnover on profitability as measured by return on assets, return on equity, and net profit margin using the firm size control variable due to the inconsistency of results and the lack of related research. 5980 observations from manufacturing companies in five ASEAN countries that published financial reports on their respective stock exchanges in the 2012-2016 period were the sample for this research. This sample was then tested for multicollinearity and heteroscedasticity first and then the multiple regression method with a fixed effect model was used to find out the influence of the independent variable on the dependent variable. The research results found that working capital turnover did not affect the profitability of manufacturing companies in ASEAN. Thus, it is recommended that companies use other liquidity strategies that can be proven to influence profitability. It is recommended that further research be carried out using other variables or in different countries and research periods.